Assessment of dendrocalamus asper (Schult and schult f.) (Poaceae) bamboo treated with tannin-boron preservatives. (3rd May 2021) - Gauss, Christian; Kadivar, Marzieh; Pereira, Ricardo G.F.; Savastano Jr., Holmer
Highlights: Acacia mearnsii tannin successfully cross-linked with hexamine and boron. Tannin-based preservatives improved fungi decay resistance of bamboo. Superior mechanical properties obtained with tannin-boron treatment. Boron compounds and tannin positively affected the thermal stability of bamboo. Abstract: Tannin-boron based preservative solutions were used for the treatment of D. asper bamboo by vacuum/pressure impregnation. Samples treated with tannin/hexamine-based solutions presented low weight losses after decay tests with P. sanguineus and G. trabeum decay fungi, and were classified as resistant and highly resistant, respectively, even after leaching. However, a high boron loss after severe leaching cycles was observed. Samples treated with tannin/hexamine/boron had superior mechanical properties and increased thermal stability. The use of tannin-based solutions in combination with boron compounds showed promising results in terms of mechanical properties improvement and increased fungal decay resistance, bringing new possibilities for bamboo preservation.